Enhanced visible light absorption and reduced charge recombination in AgNP plasmonic photoelectrochemical cell - Samaila Buda; Suhaidi Shafie; Suraya Abdul Rashid; Haslina Jaafar; N.F.M. Sharif (Results in Physics, 2017)
In this research work, silver nanoparticles (AgNP) were synthesized using a simple solvothermal technique, the obtained AgNP were used to prepare a titania/silver (TiO2/Ag) nanocomposites with varied amount of Ag contents and used to fabricated a photoanode of dye-sensitized solar cell (DSSC). X-ray photoelectron spectroscopy (XPS) was used to ascertain the presence of silver in the nanocomposite. A photoluminance (PL) spectra of the nanocomposite powder shows a low PL activity which indicates a reduced election- hole recombination within the material. UV–vis spectra reveal that the Ag in the DSSC photoanode enhances the light absorption of the solar cell device within the visible range between λ = 382 nm and 558 nm nm owing to its surface plasmon resonance effect. Power conversion efficiency was enhanced from 4.40% for the pure TiO2 photoanode based device to 6.56% for the device fabricated with TiO2/Ag due to the improvement of light harvesting caused by the localized surface plasmonic resonance effect of AgNP. The improvement of power conversion was also achieved due to the reduced charge recombination within the photoanode. Keywords: Nanoparticle, Silver, Plasmonic, Power, Photon